2014
DOI: 10.1371/journal.pone.0091143
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein-Specific Antibodies that Detect Multiple TSE Agents with High Sensitivity

Abstract: This paper describes the generation, characterisation and potential applications of a panel of novel anti-prion protein monoclonal antibodies (mAbs). The mAbs were generated by immunising PRNP null mice, using a variety of regimes, with a truncated form of recombinant ovine prion protein spanning residues 94–233. Epitopes of specific antibodies were mapped using solid-phase Pepscan analysis and clustered to four distinct regions within the PrP molecule. We have demonstrated the utility of these antibodies by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…To block for endogenous peroxidase, slides were immersed in 1% H 2 O 2 /methanol before washing in running water for 5 min followed by PBS/1% BSA wash buffer for 5 min. Sections were subsequently incubated with Normal Goat Serum (Stratech) for 20 min before application of either BH1 ([55] used at 0.02 μg/mL) or 6H4 (Prionics used at 3 μg/mL) anti-PrP antibodies. The primary antibodies were incubated overnight before washing with PBS/1% BSA wash buffer.…”
Section: Methodsmentioning
confidence: 99%
“…To block for endogenous peroxidase, slides were immersed in 1% H 2 O 2 /methanol before washing in running water for 5 min followed by PBS/1% BSA wash buffer for 5 min. Sections were subsequently incubated with Normal Goat Serum (Stratech) for 20 min before application of either BH1 ([55] used at 0.02 μg/mL) or 6H4 (Prionics used at 3 μg/mL) anti-PrP antibodies. The primary antibodies were incubated overnight before washing with PBS/1% BSA wash buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Each assay included known BSE‐positive and ‐negative control tissue sections to verify the sensitivity and specificity of the procedure. Immunohistochemical staining of rectal biopsy samples was performed as previously described, using the MoAb R145 …”
Section: Methodsmentioning
confidence: 99%
“…Proteinase K (PK)-resistant PrP Sc in brain and lymphoid tissues was detected using established Western blot methods, probing with the monoclonal antibody (MoAb) ROS-BC6 (0.5 mg/mL) as previously described. 17,54,55 Autoradiography film (Hyperfilm, GE Healthcare, Buckinghamshire, UK) was scanned and the digital image processed using a computer program (Adobe Photoshop, Adobe Systems, Inc., San Jose, CA). Image processing was restricted to cropping, preparation of composite figures, and annotation.…”
Section: Detection Of Disease-associated Prp In Tissues By Western Blmentioning
confidence: 99%
See 1 more Smart Citation
“…Series of conventional antibodies have been raised since then, with promising candidates able to cure PrP Sc in vitro with half maximal inhibitory concentration of PrP Sc (IC50) far below 1 μM [ 50 ]. The process of developing new panels of anti-PrP antibodies is still in progress [ 45 , 93 , 94 , 95 , 96 ]. A study aimed at characterizing the pharmacokinetic properties of anti-PrP antibodies with curing properties in vitro showed that their curing capacity in vivo is associated with intrinsic pharmacokinetic properties rather than their isotype, epitope or affinity [ 97 ].…”
Section: Molecular Parameters That Influence the Quality Of The Anmentioning
confidence: 99%